THE IMPACT OF CONSUMING SALMON FISH (SALMO SALAR) ON DENTAL CALCIUM LEVELS IN MICE (MUS MUSCULUS) - Sandy Christiono; Naila Salsabila; Rizki Amalina; Welly Anggarani; Islamy Rahma Hutami (Dentino : Jurnal Kedokteran Gigi, 2023)
ABSTRACTBackground: Pregnant women require calcium as a vital vitamin. Insufficient calcium intake during pregnancy can result in enamel hypoplasia and cavities in deciduous teeth. It can boost pregnant women's calcium intake with calcium-containing pill formulations and vitamin D; however, this has negative effects such as kidney stone issues. Salmon can be used as a substitute because it has no negative side effects and contains omega 3, which can enhance calcium absorption. Purpose: This study aimed to determine the effect of salmon (Salmo salar) consumption on calcium levels in the teeth of mice (Mus musculus). Method: This study used pregnant mice and a post-test-only control strategy. Pregnant mice were fed salmon combined with CMC (Carboxy Methyl Cellulose) and CMC (Carboxy Methyl Cellulose) alone as a control. The salmon dose administered is 2.17 mg/0.5 ml. Using atomic absorption spectrophotometry, mice dental calcium levels can be determined (AAS). Result: The findings of hypothesis testing with an unpaired t-test of 0.041 revealed a significant difference between the salmon-eating and CMC-consuming groups at p 0.05. (Carboxy Methyl Cellulose). Conclusion: Consuming salmon can significantly increase the calcium content of mouse teeth. Keywords: Dental calcium, Mice (Mus Musculus, Pregnant mice, Salmon (salmo nalar)